Hubungan antara Postur dan Beban Kerja dengan Kelelahan Kerja pada Pegawai Mekanik Bengkel Motor di Denpasar - Putu Ananda Angelita; Ni Wayan Rusni; Putu Nita Cahyawati (Aesculapius Medical Journal, 2023)
Work fatigue is one of many factors that cause work accidents. Some factors that affect work fatigue include physical work activities, non-ergonomic work station, forced attitudes, monotonous work, lack of calorie needs, and inappropriate work-rest time. Mechanical worker in motorcycle repair shops do many things which workload tends to be heavy and ergonomic risks such as uncomfortable body posture. This study aims to determine the relationship between posture and workload with work fatigue on mechanical employees of a motorcycle repair shop in Denpasar. The sample of this research are 50 mechanical employees of a motorcycle repair shop in Denpasar. This study used an observational analytic method with a cross sectional approach. The results are all the workers were male, most of the workers were young age (13-25 years old), and worked >8 hours per day. Most of the workers (76%) had a normal BMI and 64% had â‰¤5 years of work experience. The results of the Spearman Correlation test analyse showed that there was a significant relationship between work posture with work fatigue (p < 0.05, r = 0.364) and workload with work fatigue (p < 0.05, r = 0.378) on mechanical employee of a motorcycle repair shop in Denpasar. It can be concluded that there is a relationship between posture and workload with work fatigue on mechanical employees of a motorcycle repair shop in Denpasar. Key words: work fatigue, work posture, workload